Skin Closure with Vicryl Vs Prolene in Day Case Surgeries - Umar Jamal Khan, Nosheela Javed, Khurram Arif, Muhammad Amjad Chaudhary, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the post-operative outcomes after skin closure with Vicryl as compared to Prolene in paediatric day case surgeries. Study Design: Comparative Cross-sectional Study Place and Duration of Study: Department of Paediatric Surgery, Children Hospital, Pakistan Institute of Medical Sciences, Islamabad for six months (1st November,2021 to 30th April,2022) Patients and Methods: A total of sixty patients under the age of 12 years, who presented for day-case surgeries were divided into two groups: Vicryl (group A) and Prolene (group B). A single surgical team performed all the surgeries. The incidence of outcomes, such as pain, hematoma, infection, suture breakage and keloid formation was recorded after the procedure. At the 30th post-operative day, the scar assessment scale was used to evaluate the wound's healing. Results: Comparitive Cross-sectional study was conducted on 60 patients who underwent surgeries, having 30 in each group. Age and scar score for both the groups were compared. There was no sigfnificant difference observed for age p = 0.628 and it was significant for scars p = 0.007. Incidence of pain and infection was not statistically significant p ≥ 0.05. No hematoma, keloids and suture breakage were observed in both the sutures. Success Rate of Vicryl was 76.7% and that of Prolene was 93.3%. Success was positively correlated with scar r = 0.685. Conclusion: In our paediatric samples, we analyzed and concluded that prolene suture was better as compared to vicryl in terms of pain and infection. Keywords: Absorbable sutures, Day-case surgeries, Non-absorbable sutures, Prolene, Vicryl.